Human Rights in the Digital Age: The Indonesian Judiciary's Response to Internet Censorship and Privacy Laws (Indonesian Court and Justice Review, 2025)
The digital transformation of society has introduced new challenges to the protection of human rights in Indonesia, particularly concerning internet censorship, privacy, and freedom of expression. This study explores how the Indonesian judiciary has responded to these emerging legal and ethical dilemmas through case rulings and constitutional review. Focusing on key decisions involving the Electronic Information and Transactions (EIT) Law, data surveillance, and content regulation, the research assesses whether courts have served as defenders of digital rights or enablers of state control. Using doctrinal analysis and comparative jurisprudence, the findings reveal a cautious and often inconsistent approach by the judiciary. While some rulings affirm the right to privacy and digital expression, others uphold government-imposed restrictions in the name of public morality, national security, or religious values. The lack of a comprehensive data protection regime until recently further complicates judicial interpretations. The study argues that the judiciary’s role is critical in setting normative boundaries in the digital realm, but current jurisprudence reflects an underdeveloped rights-based framework. The novelty of this research lies in its focus on how constitutional and administrative courts grapple with 21st-century rights issues in a legal system shaped by rapid technological and political change. The study contributes to global debates on digital governance, legal adaptation, and judicial protection of rights in the digital era.